Functional Physical Training Program for Revised Physical Fitness Test of Korean Police Officers - Ji Heon Chae; Hyun-Joo Kang (Asian Society of Kinesiology, 2022)
OBJECTIVES Police officers need to maintain and improve their physical fitness in order to properly operate on the duty and ensure their own safety. A problem was raised to prepare an improvement plan according to the current status and problems of physical fitness test of the Korean police officer. Accordingly, a revised physical fitness test for new police officers will be introduced from 2023 and will be fully introduced from 2026. The purpose of this study is to introduce revised physical fitness test type including professional physical element proper for duty feature to secure the security power and physical training program for the revised physical fitness test for Korean police officers. METHODS Functional physical training program consisted of combined with health-related fitness factors and skill-related fitness factors for successfully cope with their duties which involve physical tasks. FITT principles of functional physical training program were made for circulated physical fitness test for new Korean police officers. CONCLUSIONS Police officers must be physically fit to successfully cope with their duties which involve physical tasks. The functional physical training program could help new Korean police officers maintain physical fitness including cardiorespiratory fitness, muscular fitness, agility, could be prevent a decline in performance physical capacity and occupational duties.